Activation of Hsp90-eNOS and increased NO generation attenuate respiration of hypoxia-treated endothelial cells - Presley, Tennille (American Physiological Society, 2008)
Hypoxia induces various adoptive signaling in cells that can cause several physiological changes. In the present work, we have observed that exposure of bovine aortic endothelial cells (BAECs) to extreme hypoxia (1–5% O(2)) attenuates cellular respiration by a mechanism involving heat shock protein 90 (Hsp90) and endothelial nitric oxide (NO) synthase (eNOS), so that the cells are conditioned to consume less oxygen and survive in prolonged hypoxic conditions. BAECs, exposed to 1% O(2), showed a reduced respiration compared with 21% O(2)-maintained cells. Western blot analysis showed an increase in the association of Hsp90-eNOS and enhanced NO generation on hypoxia exposure, whereas there was no significant accumulation of hypoxia-inducible factor-1α (HIF-1α). The addition of inhibitors of Hsp90, phosphatidylinositol 3-kinase, and NOS significantly alleviated this hypoxia-induced attenuation of respiration. Thus we conclude that hypoxia-induced excess NO and its derivatives such as ONOO(−) cause inhibition of the electron transport chain and attenuate O(2) demand, leading to cell survival at extreme hypoxia. More importantly, such an attenuation is found to be independent of HIF-1α, which is otherwise thought to be the key regulator of respiration in hypoxia-exposed cells, through a nonphosphorylative glycolytic pathway. The present mechanistic insight will be helpful to understand the difference in the magnitude of endothelial dysfunction.